2022
DOI: 10.1155/2022/2350063
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of COVID-19 in Tehran, Iran: A Cohort Study of Clinical Profile, Risk Factors, and Outcomes

Abstract: Background. The outbreak of coronavirus disease 2019 (COVID-19) dates back to December 2019 in China. Iran has been among the most prone countries to the virus. The aim of this study was to report demographics, clinical data, and their association with death and CFR. Methods. This observational cohort study was performed from 20th March 2020 to 18th March 2021 in three tertiary educational hospitals in Tehran, Iran. All patients were admitted based on the WHO, CDC, and Iran’s National Guidelines. Their informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…An increased risk of mortality among patients with diabetes mellitus was also showed. In line with this finding, high risk of mortality among patients with diabetes mellitus has also been reported in other studies conducted in China, Italy and New York [ 8 , 9 , 13 , 19 ]. This could be related to the fact that diabetes mellitus weakens both the innate and adaptive immune system thus patients with diabetes mellitus are prone to severe COVID-19 illness and death [ 37 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…An increased risk of mortality among patients with diabetes mellitus was also showed. In line with this finding, high risk of mortality among patients with diabetes mellitus has also been reported in other studies conducted in China, Italy and New York [ 8 , 9 , 13 , 19 ]. This could be related to the fact that diabetes mellitus weakens both the innate and adaptive immune system thus patients with diabetes mellitus are prone to severe COVID-19 illness and death [ 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…Coronavirus disease-2019 (COVID- 19) is caused by a novel coronavirus called severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and is associated with high morbidity and mortality [1]. On 11th March 2020, the World Health Organization (WHO) declared COVID-19 a pandemic, after 118,000 cases and 4291 deaths were reported in 114 countries [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Perceived Stress Questionnaire consists of 14 items, each rated on a five-point Likert scale (none, low, moderate, high, and very high) ( Hatamabadi et al, 2022 ). Ahmadian (2012) examined the validity and reliability of the Persian version of this tool, revealing internal consistency coefficients through Cronbach's alpha of 0.71 for the positive perception of controllability, 0.75 for the negative perception of controllability, and 0.84 for the overall questionnaire scores ( Ahmadian, 2012 ).…”
Section: Data Collection and Measurementmentioning
confidence: 99%
“…According to relevant reports, people with dementia are more than three times more likely to die from COVID-19 than those without dementia and about 30% of COVID-19 deaths are in people with dementia ( 64 , 65 ). A cohort study conducted in Tehran, Iran showed that Alzheimer disease were associated with a higher risk of death related to COVID-19 ( 66 ). A cohort study conducted in England showed that COVID-19 survivors with pre-existing dementia had a higher risk of hospitalization or death (age and gender adjusted HR 2.47, 1.37 to 4.44, p = 0.002) ( 67 ).…”
Section: Why Individuals With Alzheimer’s Disease Are Most Likely To ...mentioning
confidence: 99%